The Untold Stories of Methodology: Reflections on Urban Planning Methodology through a Review on Routledge Handbook of Planning Research Methods - Faraz Tahmasbi; Morteza Hadi Jaberi Moghaddam (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
This article is a review of the Routledge Handbook of Planning Research Methods. The review attempts to summarize the content of the book and to show how understanding the methodology affects the work of academics and professionals. Among other methodology books, The Routledge Handbook is a genuine reference and the reasons can be summarized as follows: Unlike other dominant sources, this book has specifically explored the relations in the field of planning and stays within the discipline. It has also attempted to promote methodology from rigid and homogeneous entities to academics to the dynamic practices in the personal, social, and professional lives of researchers. Numerous articles in the book are mostly concerned with the link between theory and practice, and to establish this link they underpin the research production process. In the end, a brief evaluation of the content of the book is made and the necessity of incorporating it into the formal planning pedagogy is stated.